Profitability Ratios and Their Influence on Stock Performance: An Empirical Study of PT Nippon Indosari Corpindo Tbk (2017–2023) - Sariyati, Sariyati; Nuryanto, Guyub; Ekonomi, Shifa Amelia (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the effect of Return On Assets (ROA), Return On Equity (ROE), and Earnings Per Share (EPS) on the stock price of PT Nippon Indosari Corpindo Tbk in the period 2017-2023. The research method uses quantitative data from financial statements and stock prices analyzed by descriptive statistical tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results showed that partially, ROA and ROE had a significant effect on stock prices, while EPS did not. However, simultaneously, these three variables have a significant effect on the company's stock price, with a coefficient of determination of 87.1%. These findings provide practical implications for investors in evaluating key financial ratios before making investment decisions and offer theoretical insights into the predictive power of profitability indicators in emerging market contexts.